Stents in coronary heart disease patients: review of the studies available - L. A. Bokeriya; I. N. Stupakov; I. V. Samorodskaya (Кардиоваскулярная терапия и профилактика)
The review presents the results of published randomized trials, registers, meta-analyses, and systematic reviews on the following clinical outcomes: mortality, incidence of repeat myocardial infarctions, repeat revascularizations and stent thromboses among patients with various forms of coronary heart disease, after implantation of noneluting, sirolimus-eluting and paclitaxel-eluting stents.